2020
DOI: 10.3390/ijms21144929
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Disorders and Metabolic Syndrome: Dysbiosis as a Key Link and Common Bioactive Dietary Components Useful for their Treatment

Abstract: Gastrointestinal (GI) diseases, which include gastrointestinal reflux disease, gastric ulceration, inflammatory bowel disease, and other functional GI disorders, have become prevalent in a large part of the world population. Metabolic syndrome (MS) is cluster of disorders including obesity, hyperglycemia, hyperlipidemia, and hypertension, and is associated with high rate of morbidity and mortality. Gut dysbiosis is one of the contributing factors to the pathogenesis of both GI disorder and MS, and restoration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 178 publications
(185 reference statements)
0
29
0
Order By: Relevance
“…Studies had shown that in rats with gastrointestinal motility disorders, there were some changes in the amino acids levels [21,22]. In this study, L-tyrosine, L-tryptophan, and L-glutamine decreased in different degrees in the gastrointestinal motility disorder model of rats (caused by atropine sulfate).…”
Section: Discussionmentioning
confidence: 52%
“…Studies had shown that in rats with gastrointestinal motility disorders, there were some changes in the amino acids levels [21,22]. In this study, L-tyrosine, L-tryptophan, and L-glutamine decreased in different degrees in the gastrointestinal motility disorder model of rats (caused by atropine sulfate).…”
Section: Discussionmentioning
confidence: 52%
“…Gut microbiota dysbiosis as well as gut microbiota-liver axis dysfunction are the contributing factors to the pathogenesis of metabolic syndrome [ 78 , 79 , 80 ]. Intestinal microbiota may be a novel drug target of metabolic syndrome, especially for those with poor oral bioavailability.…”
Section: Potent Restoration Of Intestinal Microbiota-mediated Metabolic Syndromementioning
confidence: 99%
“…Studies have shown that, in rats with gastrointestinal motility disorders, there were some changes in the amino acid levels (De Filippis et al, 2020;Liu et al, 2017). Tryptophan is an essential amino acid in the human body and the only amino acid containing an indole F I G U R E 9 Schematic diagram of the modulated metabolites and potential disturbed metabolic pathways structure.…”
Section: Amino Acid Metabolism Disordermentioning
confidence: 99%